2019
DOI: 10.5424/sjar/2019171-13561
|View full text |Cite
|
Sign up to set email alerts
|

Identification, pathogenicity and distribution of the causal agents of dieback in avocado orchards in Spain

Abstract: An increased incidence of dieback from branches in several avocado orchards in southern Spain was observed in 2014. Surveys were conducted from May to October 2014, sampling the affected branches to isolate the causal agents. A total of 68 fungal isolates, recovered from ten avocado orchards, were identified, by morphological characterisation and DNA sequencing, as belonging to the genera: Neofusicoccum parvum (50%), Colletotrichum gloeosporioides (17.6%), Neofusicoccum luteum (16.2%), Neofusicoccum australe (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…These isolates mostly belonged to the genus Fusarium , which confirms the findings by Carranza-Rojas et al (2015) who found several Fusarium species (Hypocreales), among which F. solani and F. sambucinum , to be associated with avocado root rot. Other fungal genera such as Lasiodiplodia (Botryosphaeriales), Scytalidium (Helotiales) and Mortierella (Mortierellales) have been previously reported as avocado pathogens in Peru, Spain, South Africa and Mexico ( Alama et al, 2006 ; Coertzen and Fourie, 2017 ; Hernández Pérez et al, 2018 ; Arjona-Girona et al, 2019 ). Sequencing of the fungal microbiome confirmed that Helotiales and Mortierellales were dominant taxa in the rhizosphere of root rot symptomatic trees, which suggests that these taxa could act as opportunistic fungal pathogens following root rot infection.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates mostly belonged to the genus Fusarium , which confirms the findings by Carranza-Rojas et al (2015) who found several Fusarium species (Hypocreales), among which F. solani and F. sambucinum , to be associated with avocado root rot. Other fungal genera such as Lasiodiplodia (Botryosphaeriales), Scytalidium (Helotiales) and Mortierella (Mortierellales) have been previously reported as avocado pathogens in Peru, Spain, South Africa and Mexico ( Alama et al, 2006 ; Coertzen and Fourie, 2017 ; Hernández Pérez et al, 2018 ; Arjona-Girona et al, 2019 ). Sequencing of the fungal microbiome confirmed that Helotiales and Mortierellales were dominant taxa in the rhizosphere of root rot symptomatic trees, which suggests that these taxa could act as opportunistic fungal pathogens following root rot infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the three fungal species tested in the present study are not only pathogens of grapevine, but also of other commercially important woody plants. For instance, D. seriata and B. dothidea are phytopathogens of apple [22], N. parvum causes dieback in avocado [45], B. dothidea causes branch dieback of olive [46], and the three of them are associated with branch cankers on almond trees [47]. Consequently, the results of this study may also find application in other pathosystems, resulting in an even higher ecological and economic impact.…”
Section: Discussionmentioning
confidence: 99%
“…[59], and even on woody crops of recent implantation and extension in Spain such as pistachio [60,61]. Furthermore, D. seriata and B. dothidea have been cited as phytopathogens on apple [62], while N. parvum causes avocado dieback [63], B. dothidea causes Botryosphaeria blights and cankers on olive trees [64], and as mentioned, the three of them are commonly related to branch cankers on almond trees [54]. Therefore, the findings obtained in the present study may also be applied and extended to other basic Mediterranean crops that usually share these types of pathogens.…”
Section: Significance Of the Reported Findingsmentioning
confidence: 99%